Proceedings of the 2008 International Symposium on Software Testing and Analysis 2008
DOI: 10.1145/1390630.1390664
|View full text |Cite
|
Sign up to set email alerts
|

Automatic documentation inference for exceptions

Abstract: Exception handling is a powerful and widely-used programming language abstraction for constructing robust software systems. Unfortunately, it introduces an inter-procedural flow of control that can be difficult to reason about. Failure to do so correctly can lead to security vulnerabilities, breaches of API encapsulation, and any number of safety policy violations.We present a fully automated tool that statically infers and characterizes exception-causing conditions in Java programs. Our tool is based on an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
73
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 47 publications
0
73
0
Order By: Relevance
“…In most cases, such implicit exceptions are caused by programming errors, so it might be inappropriate to include them in the documentation [15]. Therefore, we adopt a similar strategy as in [16] and omit implicit exception extraction. For static analysis tools, we use Eclipse's JDT and CallHierarchy mainly due to their ability to parse programs with incomplete reference information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most cases, such implicit exceptions are caused by programming errors, so it might be inappropriate to include them in the documentation [15]. Therefore, we adopt a similar strategy as in [16] and omit implicit exception extraction. For static analysis tools, we use Eclipse's JDT and CallHierarchy mainly due to their ability to parse programs with incomplete reference information.…”
Section: Discussionmentioning
confidence: 99%
“…For static analysis tools, we use Eclipse's JDT and CallHierarchy mainly due to their ability to parse programs with incomplete reference information. Some related work, such as [16], utilizes the Soot toolset [17], which requires complete type class references.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work from Sridhara et al automatically synthesize natural language sentences for specific types of code segments directly, including Java methods [3], groups of statements [4], Java classes [5], and parameter comments [6]. Others focus on generating documents for exception [22], failed test cases [23], and code changes [24]. A few previous work focus on mining descriptions or documentation from developer communications, such as bug reports, forum posts and emails [25], [26], [27].…”
Section: A Automatic Comment Generationmentioning
confidence: 99%
“…At best, these policies are partially documented in API documentation or source code comments. Most of the times these policies are not documented and exist as implicit rules in the source code (BUSE andWEIMER, 2008, THUMMALAPENTA andXIE, 2009). In fact, the lack of explicit exception handling policies is considered one of the main reasons why developers struggle to implement exception handling (SHAH et al, 2010).…”
Section: Lack Of Explicit Exception Handling Policiesmentioning
confidence: 99%
“…Developers participating in recent surveys reported that there exist exception handling policies in their systems, although not much e↵ort is spent in documenting them CASTOR, 2013,EBERT et al, 2015). Most of the times these policies are not documented and exist as implicit rules in the source code (BUSE andWEIMER, 2008, THUMMALAPENTA andXIE, 2009). In fact, in the study presented in Chapter 3, we observed that some faults occurred due to violations of implicit exception handling policies of the projects.…”
Section: Specifying and Verifying Exception Handling Policiesmentioning
confidence: 99%